Averaging of a multifrequency boundary-value problem with linearly transformed argument - Bigun, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We establish the existence of a solution and obtain an estimate of the error of the averaging method for a multifrequency system with linearly transformed argument and multipoint boundary conditions.